2020
DOI: 10.7150/ijbs.34517
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-335-3p by NF-κB Transcriptional Regulation Contributes to the Induction of Pulmonary Arterial Hypertension via APJ during Hypoxia

Abstract: Pulmonary arterial hypertension (PAH) is a cardiopulmonary disease that can lead to heart failure and eventually death. MicroRNAs (miRs) play essential roles during PAH progression; however, their exact mechanism of action remains unclear. Apelin is a small bioactive peptide with a key protective function in the pathogenesis of PAH mediated by binding to the APJ gene. The aim of the present study was to investigate the role of miR-335-3p in chronic normobaric hypoxia (CNH)-induced PAH in mice and the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Chronic normobaric hypoxia stimulated PAH and also increased the level of miR-335-3p in the mouse lung [91]. The inhibition of miR-335-3p resulted in the attenuation of chronic normobaric hypoxia-induced vascular remodeling and PAH in mice [91]. A significant increase in miR-30a-5p level in the plasma of PAH patients was recently reported [92].…”
Section: Pahmentioning
confidence: 82%
See 1 more Smart Citation
“…Chronic normobaric hypoxia stimulated PAH and also increased the level of miR-335-3p in the mouse lung [91]. The inhibition of miR-335-3p resulted in the attenuation of chronic normobaric hypoxia-induced vascular remodeling and PAH in mice [91]. A significant increase in miR-30a-5p level in the plasma of PAH patients was recently reported [92].…”
Section: Pahmentioning
confidence: 82%
“…Moreover, miR-27a targeted SMAD5 to promote hypoxia-induced endothelial to mesenchymal transition [90]. Chronic normobaric hypoxia stimulated PAH and also increased the level of miR-335-3p in the mouse lung [91]. The inhibition of miR-335-3p resulted in the attenuation of chronic normobaric hypoxia-induced vascular remodeling and PAH in mice [91].…”
Section: Pahmentioning
confidence: 99%
“…It has been reported that inflammation of vascular smooth muscle cells played a key role in various vascular disorders, including PAH, restenosis and atherosclerosis [13]. In terms of PAH research, a recent study noted that the up‐regulation of miR‐335‐3p mediated by NF‐κB contributes to the inhibition of apelin receptor and development of PAH [14]. Moreover, Li et al [15] found that NF‐κB‐mediated miR‐130a modulation might play a critical role in excessive lung vascular remodeling, which is a major cause of the increased pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We report the discovery of potentially pathogenic variants in TNIP2 and TRAF2, two genes associated with inflammation and immunity whose role in PAH has not been previously documented. Through the use of patient-derived cells and in vitro gene knockdown studies, we show that TNIP2 and TRAF2 act by suppressing the activation of NF-κB, a transcription complex that controls the expression of inflammatory cytokines and genes associated with cell proliferation in PAH (18)(19)(20)(21). We conclude that TNIP2 and TRAF2 pathogenic variants could increase PAH susceptibility through their capacity to alter cellular immune responses and drive abnormal cellular proliferation in the pulmonary vasculature.…”
Section: Introductionmentioning
confidence: 93%